2019
DOI: 10.1016/j.ebiom.2018.12.046
|View full text |Cite
|
Sign up to set email alerts
|

Circulating sphingolipids, fasting glucose, and impaired fasting glucose: The Strong Heart Family Study

Abstract: Background Animal studies suggest sphingolipids as an early marker of impaired glucose metabolism; however, research in humans is limited. We evaluated whether individual sphingolipid species were associated with fasting plasma glucose and incident impaired fasting glucose in a longitudinal cohort study. Methods We measured 15 sphingolipid species from blood samples collected in 2001–2003 from 2145 participants without prevalent diabetes in the Strong Heart Family Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 26 publications
(31 reference statements)
4
41
1
Order By: Relevance
“…Over the last few years, circulating sphingolipids have been gaining interest as predictive biomarkers for cardiac and metabolic disorders. Consistently, recent findings have shown that altered circulating sphingolipids were associated with defective insulin signaling [255][256][257][258][259]. The ability of sphingolipids to be trafficked from tissue to tissue using plasma lipoprotein carriers would also reveal a role for interorgan crosstalk.…”
Section: Discussionmentioning
confidence: 59%
“…Over the last few years, circulating sphingolipids have been gaining interest as predictive biomarkers for cardiac and metabolic disorders. Consistently, recent findings have shown that altered circulating sphingolipids were associated with defective insulin signaling [255][256][257][258][259]. The ability of sphingolipids to be trafficked from tissue to tissue using plasma lipoprotein carriers would also reveal a role for interorgan crosstalk.…”
Section: Discussionmentioning
confidence: 59%
“…The ORs for diabetic risk genes were less than 1.7 in genome-wide association studies 36 . A 2-fold higher ceramide-24 level was associated with 1.45 times higher risk of incident impaired fasting glucose 37 . We believe that an important factor in explaining why RRs in this study were so high was the measurement of AhRL and MIS with the cell-based bioassays.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, global metabolic mapping revealed different metabolic profiles in IF16 and EOD, with asymmetrical trigger of different milieu of carbohydrate, lipid, and protein cellular metabolic pathways, as well as performing varying degrees of anabolism and catabolism of these macromolecules. While most of the signalling pathways have been previously reported to be influenced by fasting (Ahima et al, 2006;Bujak et al, 2015;Choi et al, 2018;Dogan et al, 2011;Goldstein et al, 2016;Guo et al, 2016;Jensen et al, 2019;Kim, 2009;Li et al, 2019;Luo et al, 2018;Mahadik, 2012;Martins et al, 2016;Miyazaki et al, 2004;Morikawa et al, 2004;Nicklin et al, 2013;Pel and Lines, 2015;Rodrı et al, 2012;Tulsian et al, 2018;Wee and Wang, 2017;Wijngaarden et al, 2019;Yoon et al, 2018), our findings suggest a temporal link of the signaling response to the period of energy restriction. This is achieved by manipulating the epigenetic and transcriptomic cascade differently, which in turn results in varied metabolic arms being triggered to respond to energy demand.…”
Section: Discussionmentioning
confidence: 43%